INOVASI PEMBELAJARAN BAHASA INDONESIA MELALUI PENDEKATAN PROSES DAN MEDIA - Rinja Efendi; Radia Zulfitri; Dealani Putri; Nesha Maldini; Inneke Kusherawati; Septia Ningsih; Patri; Aldi Antoni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Effective Indonesian language learning requires innovation in approach and media used. A process approach that focuses on student activities and the use of appropriate media can improve students' Indonesian language skills. This article discusses innovation in Indonesian language learning through a process approach and media, as well as examples of its implementation in the classroom. The process approach allows students to be actively involved in the learning process, so they can develop their Indonesian language skills more effectively. Meanwhile, appropriate media can help students understand Indonesian language concepts more easily and enjoyably.